Higher Postinduction Infliximab Serum Trough Levels Are Associated With Healing of Fistulizing Perianal Crohn's Disease in Children. Issue 1 (15th June 2018) - El-Matary, Wael; Walters, Thomas D; Huynh, Hien Q; deBruyn, Jennifer; Mack, David R; Jacobson, Kevan; Sherlock, Mary E; Church, Peter; Wine, Eytan; Carroll, Matthew W; Benchimol, Eric I; Lawrence, Sally; et al.
Abstract: Background: There is some evidence in adults that higher serum infliximab (IFX) levels are needed to adequately treat fistulizing perianal Crohn's disease (CD). However, data in children are lacking. We aimed to determine postinduction serum trough IFX levels that are associated with healing of fistulizing perianal CD (PCD) at week 24. Methods: In a multicenter inception cohort study, consecutive children younger than age 17 years with fistulizing perianal CD treated with IFX between April 2014 and June 2017 who had serum trough IFX titers measured before the fourth infusion were included. Area under the receiver operating characteristic curve (AUROC) was calculated to determine the best cutoff to predict fistula healing. Results: A total of 667 children with Crohn's disease were recruited, with 85 (12.7%) patients diagnosed with fistulizing PCD. There were 27 of 52 (52%) children in whom pre–fourth infusion IFX levels were measured (mean age, 12.57 ± 5.12 years). At week 24, 14 of 27 (52%) patients responded with healing/healed PCD, whereas the rest had ongoing active fistulizing disease. The median IFX pre–fourth dose level in the responders was 12.7 ug/mL, compared with 5.4 ug/mL in the active disease group ( P = 0.02). There was a strong correlation between IFX levels and healing of fistulizing PCD at week 24 ( r = 0.65; P < 0.001). The AUROC was 0.80 (95% confidence interval, 0.64–0.97; P = 0.007) for pre–fourth IFX level to predict response of fistulizing PCD at week 24, and a level of 12.7 ug/mL best predicted fistula healing. Conclusions: Higher trough IFX levels are associated with healing of fistulizing perianal CD.